PEMBERLAKUAN ASAS BERLAKU SURUTDALAM PERKARA PEMBATALAN PERKAWINAN DI UNDANG-UNDANG PERKAWINAN - Ali Imron (Fakultas Hukum Universitas Wahid Hasyim, 2016)
The implementation of law retroactively within crime law will give more bad effects for the onewho commit the crime. It will also make the chaos of law and the vanishing of law certainty.Therefore, the retroactive act is forbidden in 1945 Constitution.In marriage law, it is stated thatthe disengage of marriage starts after the court verdict has certainty law power and the verdictapplies since the beginning of the marriage. This verdict contains the retroactive act in themeans of the disengage of marriage, that is it applies backwards since ijab qabul or thebeginning of the marriage.The disengage of marriage retroactively in certain case will givemore justice opportunity, it will also be more useful, and give a better law for related persons.The application of retroactive act is not without condition, however, it looks more on the justice dimensions, and the usefulness of the law that will be applied.Key words: Islamic law, marriage, retroactive act.